2021
DOI: 10.1111/jasp.12717
|View full text |Cite
|
Sign up to set email alerts
|

Working toward eradicating weight stigma by combating pathologization: A qualitative pilot study using direct contact and narrative medicine

Abstract: Despite an extensive body of research showing the negative consequences of weight stigma, healthcare providers (HCPs) continue to marginalize fat 1 patients through negative attitudes, stereotypical beliefs, and discriminatory actions (Daníelsdóttir et al., 2010;Phelan et al., 2015). Weight stigma is present through all stages of medical training, where derogatory comments about fat patients abound (see Flint, 2015). It is therefore imperative to combat weight stigma early in medical education. Reviews of weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Based on these arguments (among others), several leading medical organizations have formally recognized obesity as a chronic disease (e.g., World Obesity Federation, American Medical Association; Bray et al, 2017). However, critics have argued that recognizing obesity as a disease may increase weight-based rejection, particularly if it leads health professionals to rely more on weight as a heuristic for health (NAAFA, n.d.;Fox et al, 2021). In this context, health professionals may focus on weight management as a proxy for health management, which could be discriminatory if weight-related advice is unsolicited or leaves other health issues pertinent to the patient going untreated (Amy et al, 2005;Moore, 2014).…”
Section: Does Pathologizing Obesity Reduce Weight-based Rejection?mentioning
confidence: 99%
“…Based on these arguments (among others), several leading medical organizations have formally recognized obesity as a chronic disease (e.g., World Obesity Federation, American Medical Association; Bray et al, 2017). However, critics have argued that recognizing obesity as a disease may increase weight-based rejection, particularly if it leads health professionals to rely more on weight as a heuristic for health (NAAFA, n.d.;Fox et al, 2021). In this context, health professionals may focus on weight management as a proxy for health management, which could be discriminatory if weight-related advice is unsolicited or leaves other health issues pertinent to the patient going untreated (Amy et al, 2005;Moore, 2014).…”
Section: Does Pathologizing Obesity Reduce Weight-based Rejection?mentioning
confidence: 99%
“…A truly abolitionist reconstitution of narrative medicine would travel even further to actively restore narrative power to the people, the way narrative medicine alumna Rachel Fox did when she conducted workshops with medical students and fat activists in the community. These workshops were not a performative stunt; they were an authentic action to reduce weight stigma (Fox et al . 2021).…”
Section: Radical Inclusionmentioning
confidence: 99%
“…7 "The norms of narrative competence govern the interaction with the patient in a way sensitive to a whole host of cultural, emotional, and contextualized aspects" (Vannatta and Vannatta 2013, p. 43) and help physicians fully understand the stories of their patients including the implicit meaning of narratives (Kalitzkus and Matthiessen 2009;Vannatta and Vannatta 3 Crawford (2021) also remarks that "compassion takes empathy one step further by taking some sort of action to try to help the suffering". 4 See also Mc Donald et al (2015) on the role of the implicit memory in the link between fiction reading and the development of empathy and Fox et al (2020) on psychological research regarding one's own extended effortful cognitive processing and the shaping of future behavior in the long term. 5 A representative example is Zunshine (2006Zunshine ( , 2010.…”
Section: Literary Reading and Empathy In Medicinementioning
confidence: 99%
“…In the study of Lancaster et al (2002) students reported increased empathy as the most valuable aspect of the close reading of literature on specific themes. Fox et al (2020) also showed that the practice of close reading was tied to the skill of perspective-taking as the analysis of their workshop texts helped medical students generate empathy and craft strategies for combating weight stigma in their own future medical practice. Two recent studies of the use of narrative medicine programmes in pediatric psycho-oncology and palliative care also support the use of narrative medicine to foster empathic behaviors (Lorenz et al 2021;Sagin et al 2021 respectively).…”
Section: Literary Reading and Empathy In Medicinementioning
confidence: 99%